CRISPR-Cas13a as a next-generation tool for rapid and precise plant RNA virus diagnostics - Marzieh Karimi; Abozar Ghorbani; Ali Niazi; Mahsa Rostami; Ahmad Tahmasebi (Plant Methods)
Abstract Plant viruses are among the most serious threats to global agriculture, causing significant yield losses and jeopardizing food security. Identifying these viruses is crucial to prevent widespread crop damage and ensure effective management. CRISPR-Cas13a, a subtype of the RNA-targeting Cas13 family, has emerged as a transformative tool in molecular diagnostics, specifically tailored to detect these plant RNA viruses with unparalleled precision. Unlike traditional methods such as ELISA and RT-PCR, which are often limited by sensitivity, equipment dependency, and long processing times, Cas13a offers exceptional specificity and attomolar-level sensitivity. Its RNA-guided collateral cleavage mechanism allows signal amplification, making it particularly suitable for field-deployable diagnostics. Recent advances in Cas13 engineering, including compact variants such as Cas13bt3 and Cas13Y, have further improved its delivery efficiency and minimized immune responses, enhancing its agricultural applications. Integration with amplification methods like LAMP and innovative biosensor platforms like graphene-based and electrochemical systems further enhances its diagnostic potential. While challenges remain, including off-target effects, reagent stability, and scalability, innovations in CRISPR RNA (crRNA) design, reagent encapsulation, and microfluidic technologies are actively addressing these barriers. CRISPR-Cas13a represents a cutting-edge solution for rapid, accurate, and accessible plant virus diagnostics, providing a powerful safeguard for crop yields and global food security.